The Red and Orange Complex Subgingival Microbiome of Cognitive Impairment and Cognitively Normal Elderly with Periodontitis - Fatimah Maria Tadjoedin; Sri Lelyati C. Masulili; Muhammad Ihsan Rizal; Lindawati S. Kusdhany; Yuda Turana; Raden Irawati Ismail; Boy M. Bachtiar (Geriatrics, 2022)
Increasing evidence has shown an association between periodontitis and cognitive impairment. Subgingival microbiota play a great role in periodontitis pathogenesis. However, the correlation between the subgingival microbiome and cognitive impairment remains unclear. This study aimed to evaluate the red and orange complex subgingival microbiome of cognitively impaired and cognitively normal elderly Indonesian subjects with periodontitis. Twenty-eight elderly subjects diagnosed with periodontitis underwent two cognitive examinations using the Hopkins Verbal Learning Test and the Mini-Mental State Examination. Gingival crevicular fluid taken from the periodontal pocket, at a depth between 5 and 7 mm, using a paper point was used as the subgingival samples. The subgingival microbiome in the cognitive impairment group (n = 14) and cognitively normal group (n = 14) was compared using the 16S rRNA Metagenomic iSeq™ 100 Sequencing System. There was β-diversity in the subgingival microbiota between the cognitively impaired and cognitively normal subjects. The metagenomic analysis showed a higher abundance of Porphyromonas and Treponema bacteria in the cognitive impairment group than in the normal cognitive group (p < 0.05). The abundance of Porphyromonas gingivalis and Treponema denticola was higher in the cognitively impaired elderly subjects. The role of P. gingivalis and T. denticola in the pathogenesis of cognitive impairment needs further investigation.